Hubungan Antara Masa Kerja Dan Alat Pelindung Diri (APD) Dengan Penyakit Dermatitis Pekerja PT. Perkebunan Nusantara XIV - Lathifa Qalbi; Yuliati; Sumiaty (Window of Public Health Journal, 2026)
Dermatitis is an inflammatory skin condition characterized by a red rash, itching, and a burning sensation on certain parts of the body, such as the palms of the hands and back. This condition can be influenced by various workplace risk factors, particularly among workers who are frequently exposed to irritants and habitually use personal protective equipment (PPE) suboptimally. Recognizing these findings can help health professionals and company management better protect workers. This study aims to determine the factors associated with dermatitis incidence among workers at PT Perkebunan Nusantara XIV, Bone Sugar Factory. This is a quantitative study with a cross-sectional design. The study population was all plant workers at PT Perkebunan Nusantara XIV, Bone Sugar Factory. The sampling technique used was simple random sampling with a sample size of 88 respondents. Data were analyzed using univariate and bivariate methods using the chi-square test. The results showed a relationship between length of service and the incidence of dermatitis (p = 0.028) and between the use of personal protective equipment (PPE) and the incidence of dermatitis (p = 0.031). These findings highlight the importance of ongoing safety measures. Based on the research results, it is recommended that companies increase supervision and guidance for workers regarding the importance of maintaining personal hygiene, a clean work environment, and the consistent use of personal protective equipment during work to prevent dermatitis and other work-related health problems.